Pediatric Spinal Cord Injury: Recognition of Injury and Initial Resuscitation, in Hospital Management, and Coordination of Care - Lemley, Kyle; Bauer, Paul (Journal of Pediatric Intensive Care, 2015)
Spinal cord injury is uncommon in the pediatric population with a lifelong impact for the patient and family. Knowledge of spine embryology, mechanisms of injury that lead to specific injuries, appropriate utilization of radiographic imaging based on suspected injury, prehospital and hospital management of various spinal cord injuries is essential for providers attending to traumatically injured patients. In addition to patients who present with soft tissue and bony injuries diagnosed with clinical examination and confirmed with computed tomography or magnetic resonance imaging, it is important to note that the pediatric population is at a higher risk for spinal cord injury without radiographic abnormality than the adult population. Patients who survive the acute phase of injury face long-term rehabilitation and have an increased risk of depression and mortality. Understanding the long-term sequelae of spinal cord injuries is also an essential management component of traumatically injured children. A program that provides long-term rehabilitation, psychosocial and spiritual support, and adaptive environmental supports gives patients and their families the best opportunity for long-term recovery. A review of the current literature on the diagnosis, management, and follow-up of pediatric spinal cord injury is presented.
Keywords: spinal cord injury; spinal cord injury without radiographic abnormality; spinal shock; neurogenic shock